P215 Effects of ARNI therapy on left atrial and ventricular longitudinal deformation and functional capacity in HFrEF patients. (17th January 2020) - Mandoli, G E; Spera, L; Giannoni, A; Cassano, F; Incampo, E; Borrelli, C; Sciarrone, P; Taddei, C; Emdin, M; Mondillo, S; Cameli, M
Abstract: Background: valsartan and sacubitril combination (angiotensin receptor-neprilysin inhibitor, ARNI) was superior, in randomized trials, to lone ACE inhibitors in terms of reduction of cardiovascular mortality rate and hospitalization for acute heart (HF) in patients with HF with reduced ejection fraction (HFrEF). Purpose: the main goal of our study was to assess the effects of ARNI on left atrial (LA) and left (LV) and right ventricular (RV) function, evaluated by standard and speckle tracking echocardiography (STE), and on patients' functional capacity by cardiopulmonary exercise testing (CPET), in patients with HFrEF. Methods: we prospectively enrolled 16 patients with a LV EF ≤35% and >18 years old, in two different centers with high expertise in HF management. Exclusion criteria included: symptomatic hypotension, stage IV renal failure (eGFR < 30 ml/min/1.73 m2), ACE-inhibitor (ACEi) intolerance or previous angioedema, poor acoustic window, refuse to participate to the study. At enrollment (T0), all patients were in therapy with ACEi or sartans (ARBs) and underwent physical examination, ECG, blood test (including NT-proBNP), standard echo, STE and CPET. We shifted therapy from ACEi/ARBs according to HF guidelines and we repeated all tests after 6 months. Results: population had an average age of 63 ± 9 years, 94% was males. Etiology was ischemic in one third of the subjects. At 6 months follow up, NT-proBNP was significantly lower (512.2 ± 518.5 vs 431.2 ± 330.1 ng/l, p 0, 001) together with reduced LV filling pressure evaluated by E/A ratio and E/e' ratio (11.2 ± 8.6 vs 8.8 ± 4.8, p 0.01). LV EF improved from 31.7 ± 3.4% to 36.2 ± 7.2% (p 0.01) and LV dimensions decreased. LV global longitudinal strain (GLS) did not change significantly while free wall RV GLS increased from – 20.4 ± 6.3% to – 24.6 ± 9%, p 0.001, as peak atrial longitudinal strain (PALS) did (16.1 ± 2.6% vs 27.6 ± 4.1%, p 0.001). Between CPET indexes, only VE/VCO2 slope improved but only with borderline statistical significance (32.7 ± 5.3 vs 29.7 ± 6.8, p 0.05, Fig. 1). Conclusions: this preliminary study evaluated for the first time the effects of ARNI on echocardiographic and CPET parameters at the same time. Our results could explain the favorable clinical benefits of ARNI therapy in HFrEF: improved biventricular function, lower LV filling pressure and a more efficient ventilatory response during effort.